The Guideline’s Performance Assessment Rubric for Wind Band - Tissadikun, Natsarun (Rangsit Music Journal, 2021)
The Guideline’s Performance Assessment Rubric for Wind Band. The objective is to apply the principles of the four elements of the combined rehearsal skills of wind band, comprising Tone Quality, Tuning, Techniques and Music Expression. By using these four components to create a tool for Performance assessment rubric the actual situation to be used to measure and evaluate the performance assessment for wind band at the student level in Thailand. And able to know the level of ability and potential of integration, and realize the skills of development and improvement. The results of this study will help to improve student’s practical skills. From the performance assessment rubric tools presented to guide the above with both principles and measurement tools obtained from the prototype of United States of America’s wind band are applied to create and analyze, as well as explain the details of each key issue. That provides knowledge, understanding of each of the criteria set in the instrument, and determining the stage of the instrumental ability to know the performance potential of the wind band at what level and needs to be improved. Editing and developing playing skills in accordance with the issues of the criteria can be met with clear goals. This affects the quality of musical instruments that will effectively set the standards for the student-level wind band in Thailand.